PENINGKATAN KOMPETENSI PELAKU USAHA SOUVENIR DALAM MENGHADAPI PERSAINGAN INDUSTRI PARIWISATA DI DESA BENOA - Fahmi Tanjung; Putu Ratna Windusara Putri; I Made Wisnu Wardana; I Made Sujana (Nusantara Hasana Journal, 2023)
The increasingly competitive tourism industry requires souvenir business owners to possess adequate competencies to maintain and enhance their business competitiveness. Benoa Village, as one of the tourism-supporting areas in Badung Regency, hosts numerous souvenir businesses that depend on tourist visits. However, many business owners still face challenges such as limited product innovation, low utilization of digital technology, and insufficient marketing and business management skills. This community service program aimed to improve the competencies of souvenir business owners through structured training and mentoring activities. The methods included socialization, entrepreneurship training, digital marketing training, business management strengthening, and product development assistance. The program involved 30 souvenir business owners in Benoa Village. The results demonstrated significant improvements in participants’ understanding of marketing strategies, product innovation, business management, and the utilization of digital media for product promotion. Furthermore, participants were able to develop more adaptive business strategies in response to tourism market changes. This program contributed positively to enhancing the capacity of souvenir businesses to compete effectively and sustainably within the tourism industry.